Complex de novo chromosomal rearrangement at 15q11–q13 involving an intrachromosomal triplication in a patient with a severe neuropsychological phenotype: Clinical report and review of the literature. (22nd October 2014) - Castronovo, Chiara; Crippa, Milena; Bestetti, Ilaria; Rusconi, Daniela; Russo, Silvia; Larizza, Lidia; Sangermani, Roberto; Bonati, Maria Teresa; Finelli, Palma
<x xml:space="preserve">Abstract</x> Interstitial triplications of 15q11–q13, leading to tetrasomy of the involved region, are very rare, with only 11 cases reported to date. Their pathogenicity is independent of the parental origin of the rearranged chromosome. The associated phenotype resembles, but is less severe, than that of patients bearing inv dup(15) marker chromosomes. Here, we describe a boy of 3 years and 9 months of age who exhibited very mild craniofacial dysmorphism (arched eyebrows, hypertelorism, and a wide mouth), developmental delay, generalized hypotonia, ataxic gait, severe intellectual disability, and autism. Array comparative genomic hybridization (CGH) analysis identified a heterozygous duplication of 1.1 Mb at 15q11.2 (between low‐copy repeats BP1 and BP2), and a heterozygous triplication of 6.8 Mb at 15q11.2–q13.1 (BP2–BP4). Both acquisitions were de novo and contiguous. Microsatellite polymorphism analysis revealed the maternal origin of the triplication and the involvement of both maternal chromosomes 15. Furthermore, fluorescence in situ hybridization (FISH) analysis using BAC clones revealed that the rearrangement was complex, containing three differently sized tandem repeats of which the middle one was inverted. Our study confirms and extends the model proposed to explain the formation of intrachromosomal triplications through recombination events between non‐allelic duplicons. The comparison of the proband's clinical presentation with those of previously described cases attests the existence of endophenotypes due to the parental origin of the 15q11–q13 triplicated segment and suggests a timetable for achievement of developmental milestones, thereby contributing to improved genotype–phenotype correlations. © 2014 Wiley Periodicals, Inc.